Oral health habits during COVID-19 pandemic in university medical students - Bellini, Pierantonio; Sabatini, Silvia; Nasi, Milena; Dall'olio, Lucia; Generali, Luigi; Mecugni, Daniela; Consolo, Ugo; Mattioli, Anna Vittoria (Progress in Nutrition, 2022)
Background: The recent coronavirus disease 2019 (COVID-19) pandemic has strongly affected the young population, with a significant impact on their habits. The present study aimed to explore the effects of COVID-19 on oral health and general hygiene habits in a cohort of undergraduate students during the lockdown period in march 2020. Methods: A total of 500 under-graduate students with a mean age of 22.84 ± 2.68 years completed an anonymous web survey. We compared 2 groups: students belonging to dentistry and dental hygiene school and students belonged to nursing school. Results: The 75 % of students self-reported an increased stress and 80% were concern about the future. A reduction in personal and dental hygiene (8% and 4%, respectively) was observed. Students in dentistry and dental hygiene courses were more careful about their dental hygiene. Interestingly, students from the dentistry and dental hygiene courses reported an increase in the use of chlorhexidine mouthwash during quarantine due both to an increased frequency of use and to a switch to chlorhexidine mouthwash from others type of mouthwash. This change was probably due to the knowledge of some studies that supported the efficacy of chlorhexidine mouthwash in fighting the COVID-19 infection Conclusion: Pandemic-related stress has affected our students’ population, with changes in general and dental hygiene habits. Strong action must be taken to promote good oral hygiene habits and a healthy lifestyle among the students’ population after the COVID-19 pandemic.